Uma contribuição ao estudo de eficiência energética em sistemas industriais de ventilação - Belinovski, Kleber David (2011)
The objective of this document is to provide a method of analysis and verification of energy efficiency and power quality in industrial ventilation systems. Firstly, the motivation, procedures, methodologies used and a description of the work bench are presented. Analyses are directed specifically to the centrifugal fan installed in the Faculty of Electrical Engineering - UFU. The analysis consists of the substitution of inefficient and obsolete equipment by other modern and efficient, especially standard motors for motors of high efficiency and modernizing the control of air flow with the introduction of frequency inverter. The energy efficiency study examines the consumption of the system for these situations. The power quality study checks disturbances caused by the ventilation system when it is driven by frequency inverter. It also examines its behavior when subjected to non-ideal source and the influence of this event in total system efficiency. Finally, methods for economic analysis of investments will be presented, and a case study.